EU Regular Economic Report 8 : Living Up to Potential in the Wake of Adverse Shocks : Part 2 - Growth Over the Next Decade - World Bank (Washington, DC : World Bank, 2022)
This report discusses long-term growth prospects in four EU countries — Bulgaria, Croatia, Poland and Romania. It brings together the key anticipated structural trends in the EU over the next decade to construct a baseline for potential growth by 2030. Thereafter, it quantifies the impact of policy reform scenarios on potential growth. These reforms have been selected based on the most pressing needs for longer-term growth in the four focus countries, national targets and plans—with modeling constraints also a key consideration. These reforms include: (i) boosting labor force participation to counter the effects of an ageing population; (ii) increasing the average years of education; (iii) improving EU fund absorption rate to enhance investments; (iv) increasing the index of institutional quality to demonstrate the impact of strengthening institutions; and (v) increasing research and development (R&D) spending to accelerate the digital transition. The report also quantifies the combined impact of these reforms and their effect on the convergence process.